Research in consumer behavior. Vol. 13 - Belk, Russell W. (Emerald, 2011)
Research in Consumer Behavior presents cutting edge consumer research, whether empirical or conceptual, qualitative or quantitative. The majority of papers in this volume have been selected from the best papers at the 2011 Consumer Culture Theory Conference held in Chicago Illinois in July, 2011. The Conference is the premier event for consumer culture research which tends to be qualitative, ethnographic, and cultural in orientation and draws a variety of scholars from around the world. Many of these scholars are housed in academic marketing department, but they also come from fields of anthropology, sociology, cultural studies, and communications as well as from industry. The papers selected for this volume are those judged to be the best among those selected for the conference from submissions to the conference peer review. This marks the third volume of Research in Consumer Behavior that has been able to publish the top Consumer Culture Theory papers.
Keywords: Consumer behavior -- Research.; Business & Economics -- Consumer Behavior.; Business & Economics -- General.; Sales & marketing.; Market research.; elektronické knihy; electronic books